Fluorescent quantum dots: An insight on synthesis and potential biological application as drug carrier in cancer - P. Tandale; Neeraj Choudhary; Joga Singh; Akanksha Sharma; Ananya Shukla; Pavani Sriram; Udit Soni; Neha Singla; Ravi P. Barnwal; Gurpal Singh; Indu Pal Kaur; Ashish Suttee (Biochemistry and Biophysics Reports, 2021)
Quantum dots (QDs) are nanocrystals of semiconducting material possessing quantum mechanical characteristics with capability to get conjugated with drug moieties. The particle size of QDs varies from 2 to 10 nm and can radiate a wide range of colours depending upon their size. Their wide and diverse usage of QDs across the world is due to their adaptable properties like large quantum yield, photostability, and adjustable emission spectrum. QDs are nanomaterials with inherent electrical characteristics that can be used as drug carrier vehicle and as a diagnostic in the field of nanomedicine. Scientists from various fields are aggressively working for the development of single platform that can sense, can produce a microscopic image and even be used to deliver a therapeutic agent. QDs are the fluorescent nano dots with which the possibilities of the drug delivery to a targeted site and its biomedical imaging can be explored. This review is mainly focused on the different process of synthesis of QDs, their application especially in the areas of malignancies and as a theranostic tool. The attempt is to consolidate the data available for the use of QDs in the biomedical applications.